Review of the southern South American Macrodactylini (Coleoptera: Scarabaeidae: Melolonthinae) with descriptions of new genera and species - Smith, Andrew B.t.; Mondaca, José (Zootaxa, 2015)
The tribe Macrodactylini (Coleoptera: Scarabaeidae: Melolonthinae) is reviewed from southern South America.  A total of 13 genera and 33 species were found in the study area consisting of Argentina from Neuquén south and Chile from IV Región de Coquimbo south. The following three new genera are described: Extenuoptyophis, Insimuloissacaris, and Neuquenodactylus.  The following 11 new species are described: Ampliodactylus elguetai, Ampliodactylus guinezi, Ampliodactylus inusitus, Ampliodactylus panguipullensis, Extenuoptyophis horridulus, Extenuoptyophis metropolitensis, Insimuloissacaris nahuelbutensis, Issacaris falsa, Issacaris sola, Neuquenodactylus ramus, and Phytholaema fenestra. The species Schizochelus modestus Philippi, 1861 is transferred to the genus Ampliodactylus. Lectotypes are designated for the following five species-group names (species names given in their original combination): Dicrania aeneobrunnea Philippi, 1861, Modialis prasinella Fairmaire & Germain, 1860, Phytholaema elaphocera Redtenbacher, 1868, Phytholaema herrmanni Germain, 1901, and Schizochelus modestus Philippi, 1861.  Neotypes are designated for the following four species-group names (species names given in their original combination): Acanthosternum splendens Philippi, 1861, Areoda mutabilis Solier, 1851, Issacaris petalophora Fairmaire, 1889, and Phytholaema flavipes Philippi, 1861. The genera Modialis Fairmaire & Germain, 1860 and Phytholaema Blanchard, 1851 are here transferred to the tribe Macrodactylini. The species-group names Phytholaema pallida Saylor, 1937 and Phytholaema peccans Blackwelder, 1944 are placed in synonymy with Phytholaema herrmanni Germain, 1901. Descriptions or diagnoses, keys, and distributional data are given for all species.